2022
DOI: 10.1155/2022/4416439
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Bioinformatics Analysis of the Characteristics and Correlation of m6A Methylation in Breast Cancer Progression

Abstract: Growing cutting-edge study has demonstrated the RNA m6A methylation’s critical role in regulating tumorigenesis and progression all over the world, while it is still a mystery whether RNA m6A methylation has a positive impact on breast cancer treatment. In this article, we utilize bioinformatics to analyze three data sets including TCGA-BRCA, GSE96058, and GSE25066 and discover that breast cancer samples could be divided into 4 subtypes, which are quiescent, m6A methylation, protein-binding, and mixed, clarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The 29 m6A methylation-related genes were selected based on previous studies [24][25][26][27][28][29][30] . These genes were applied to compare the expression levels between the subgroups using limma, reshape2, ggplot2 and ggpubr R packages.…”
Section: Analysis Of M6a Methylationmentioning
confidence: 99%
“…The 29 m6A methylation-related genes were selected based on previous studies [24][25][26][27][28][29][30] . These genes were applied to compare the expression levels between the subgroups using limma, reshape2, ggplot2 and ggpubr R packages.…”
Section: Analysis Of M6a Methylationmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%